2007
DOI: 10.1016/j.chembiol.2007.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Potentiation of Fibroblast Growth Factor Activity by Synthetic Heparin Oligosaccharide Glycodendrimers

Abstract: Heparin is a highly sulfated polysaccharide that regulates a variety of cellular processes by interaction with a host of proteins. We report the preparation of synthetic heparin oligosaccharide glycodendrimers and their use as heparin mimetics to regulate heparin-protein interactions. The multivalent display of sugar epitopes mimics the naturally occurring glycans found on cell surfaces and enhances their binding capacity. Binding of the heparin dendrimers to basic fibroblast growth factor (FGF-2) was analyzed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
51
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(51 citation statements)
references
References 53 publications
0
51
0
Order By: Relevance
“…However, for compound 4, even for the third generation, a near-maximum occupancy was achieved. In comparison, using conventional amide coupling conjugation, only 8 of 32 sites were occupied by a hexasaccharide on a PAMAM dendrimer (36). The average numbers of attached oligomannose per dendron are summarized in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, for compound 4, even for the third generation, a near-maximum occupancy was achieved. In comparison, using conventional amide coupling conjugation, only 8 of 32 sites were occupied by a hexasaccharide on a PAMAM dendrimer (36). The average numbers of attached oligomannose per dendron are summarized in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…Over the past several years, many groups have found that glycodendrimers/ glycodendrons exhibit strikingly enhanced affinity against target proteins (23,31,32). More recently, different synthetic approaches and applications of these macromolecules have been explored (33)(34)(35)(36).…”
mentioning
confidence: 99%
“…Several methods have been developed to study GAG-protein interactions, including affinity chromatography, analytical ultracentrifugation, electrophoretic mobility shift assays, competition experiments, mass spectrometry-based approaches, isothermal titration calorimetry, and surface plasmon resonance (9)(10)(11)(12)(13)(14)(15)(16). Although powerful, these approaches are low throughput, often labor intensive, and require significant quantities of carbohydrate and/or protein.…”
mentioning
confidence: 99%
“…Thus, we analyzed the binding profile of CCL20 to a heparin-like carbohydrate library, which contains carbohydrates with various sulfation patterns ranging from monosaccharides to hexasaccharides (Fig. 3A) by our glycan microarray system (18,19). The screening results showed that CCL20 strongly bound to hexasaccharides 1, 2, and moderately bound to hexasaccharide 5 and tetrasaccharide 7.…”
Section: Interruption Of Lymphocyte Trafficking Pathway Attenuates Asmentioning
confidence: 99%
“…Nevertheless, the nontemplate nature of long carbohydrate chains (<25,000 disaccharide units) and conformational plasticity still make it difficult to identify the common sequences of heparan sulfate that display affinity to specific chemokines. In this regard, our previously established glycan microarray system (18,19) is a powerful tool to define the selectivity in heparan sulfate-chemokine interactions.…”
mentioning
confidence: 99%